Work practices linked to seropositive leptospirosis among cattle farmers in Northeastern Malaysia - Daud, Aziah; Basri, Ijlal Syamim Mohd; Fuzi, Nik Mohd Hafiz Mohd; Shafei, Mohd Nazri; Mohammad, Wan Mohd Zahiruddin Wan; Ismail, Nabilah; Amran, Fairuz (International Journal of Public Health Science (IJPHS), 2025)
Leptospirosis is a re-emerging zoonotic disease with significant global health implications, particularly in tropical and subtropical regions. In Malaysia, the warm, humid climate and frequent exposure to livestock and contaminated environments increase the risk of infection, especially among agricultural workers. Cattle farmers regularly handle animals and work in unsanitary conditions, which puts them at heightened risk. This study aimed to determine the prevalence of leptospirosis seropositivity and identify risk factors associated with contracting leptospirosis among cattle farmers in Northeastern Malaysia. A cross-sectional study was conducted involving 120 cattle farmers in Northeastern Malaysia. Data were collected through an interviewer-guided questionnaire, and serological testing was performed using the microscopic agglutination test with a seropositive cut-off titre of ≥1:100. The prevalence of leptospirosis seropositivity was found to be 72.5%. Significant risk factors included working with a wounded hand (Adj. OR: 7.26; 95% CI: 2.61-20.18; p<0.001), working with a wounded leg (Adj. OR: 8.52; 95% CI: 1.98-36.66; p=0.004), not wearing rubber gloves (Adj. OR: 3.96; 95% CI: 1.13-13.91; p=0.032), and not showering immediately after work (Adj. OR: 6.04; 95% CI:1.69-21.62; p=0.006). The high seroprevalence of leptospirosis among cattle farmers indicates a significant occupational risk. Future prevention programs should prioritize promoting safe work practices to mitigate this risk.